Elucidating the chemistry of particulate and chlorinated nitrates in the troposphere through method development, and chamber and field studies ... - Garner, Natasha Michelle (Science, 2020)
This thesis explores the chemistry of chlorinated and particulate nitrogen oxides in the troposphere which can impact the budgets of atmospheric oxidants and aerosol. Mixing ratios of nitryl chloride (ClNO2) were measured by chemical ionization mass spectrometry (CIMS) during the ORCA campaign in July 2015 on the west coast of Vancouver Island. Mean ClNO2 mixing ratios were small (< 10 pptv) with a maximum of 46 pptv, in part due to low precursor concentrations, i.e., of nitrogen dioxide (NO2) and ozone, and large nitrate radical sinks, e.g., titration by monoterpenes. Concentrations of ClNO2 were enhanced in air masses with elevated NO2 concentrations that had resided over the ocean, demonstrating the potential of ClNO2 to affect radical budgets in remote environments. The potential loss of ClNO2 by uptake on inorganic and secondary organic aerosol (SOA) was investigated in a newly constructed smog chamber. Uptake probabilities (γ) were determined by box modeling constrained to measured ClNO2 mixing ...